English Language Listening Proficiency in a Remote Archipelagic Context: A Mixed-Methods Case Study - Punggulina Andawaty Tiven; Wenssy Steva Nussy (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Developing EFL listening comprehension in isolated territories remains an arduous task due to severe digital divide constraints and minimal target language exposure. Posing a critical need to understand how students navigate these barriers within archipelagic education contexts, this study examined listening proficiency, metacognitive awareness, and environmental obstacles at a frontier satellite campus. Sixty undergraduate students completed an objective listening assessment and a metacognitive questionnaire, supplemented by semi-structured interviews with ten participants experiencing the realities of remote learning. Diagnostic data revealed a moderate-low performance average, where listening scores linked positively with focused attention but dropped significantly when students relied heavily on mental translation. Qualitatively, participants suffered from vocabulary-processing friction, accent anxiety, and internet-disruption fatigue. Ultimately, expanding communication competence in marginalized borders requires transitioning from online-dependent models toward localized, offline-first instructional materials that combine explicit cognitive training with culturally responsive, human-in-the loop AI tools, which are presented here as a practitioner-level framework awaiting empirical validation. Keywords: EFL listening comprehension, metacognitive awareness, archipelagic education, digital divide, remote learning